PREDIKSI KEBUTUHAN ENERGI LISTRIK DI SULAWESI UTARA : SEBUAH STRATEGI IMPLEMENTASI - Raymond Lumintang; Tritiya Arungpadang; Charles Ch Punuhsingon (JURNAL POROS TEKNIK MESIN UNSRAT, 2018)
The purpose of this research is to design the implementation strategy of electric energy requirement in sulawesi uatra by using SWOT analysis. Method of auxiliary devices used as a tool tool aids electrical energy demand analysis using artificial neural network analysis. From SWOT analysis result, SWOT parameter values are: Strength 1.65, Weaknesses 0.95, Opportunity 1.75, Threats 1.05.            The results of the SWOT analysis show that the types of threats that must be considered is the uncertainty of primary energy, especially gas, and the weakness is the limited power and networks that have not been able to reach the suluttenggo region especially the archipelago.Keywords: SWOT Analysis, Design Implementation Strategy, Prediction Electrical                   Energy Requirement